THE INFLUENCE OF SMALL GROUP DISCUSSION TOWARD STUDENTS’ PRESENTATION SKILL OF HORTATORY EXPOSITION TEXT IN SMA NEGERI 1 KEBOMAS - Permatasari, Nikmah Amelya (Universitas Muhammadiyah Gresik, 2017)
This study investigated the significant effect of small group discussion toward students’ presentation skill of hortatory exposition text. The design of the study was quasi experiment. The researcher chose the eleventh grade of SMAN 1 Kebomas which totally consist of 46 students. The sample was divided into two groups. XI-MIPA-1 was as the experiment group and XI-MIPA-2 was as the control group. The data was collected by using tests, pretest and posttest. The research finding showed that there was difference between experiment group who were taught by small group discussion method and control group who were taught by peer discussion. It is proven by the result of sig. (2tailed) is 0.039 and 0.038. The sig. (2tailed) is lower than 0.05 but it closer to 0.05. So, the null hypothesis can be rejected. It means that small group discussion gave positive effects on students’ presentation skill. The researcher concluded that small group discussion gave positive effect on students’ presentation skill. They were better in developing paragraph and better in word choices.